Senile chorea treated by deep brain stimulation: a clinical, neurophysiological and functional imaging study. - Yianni, J; Nandi, D; Bradley, K; Soper, N; Gregory, R; Joint, C; Stein, J; Scott, R; Aziz, T (2004)
We report on a patient with senile chorea, treated with deep brain stimulation of the left globus pallidus internus and subsequently the left ventralis oralis posterior nucleus of the thalamus. Deep brain field potential recordings and functional imaging using single photon emission tomography enabled us to suggest pathophysiological mechanisms for the symptoms.